2015
DOI: 10.1109/jsen.2014.2379113
|View full text |Cite
|
Sign up to set email alerts
|

EMF Signature for Appliance Classification

Abstract: Various intrusive and nonintrusive appliance load monitoring and classification systems have been studied; however, most of them designed so far provide group-level energy usage feedback. We present the first phase of a system with the potential to attribute energy-related events to an individual occupant of a space and provide occupant-specific energy usage feedback in an uninstrumented space (e.g., home or office). This initial phase focuses on collecting the electromagnetic field (EMF) radiated by several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
(13 reference statements)
0
8
0
1
Order By: Relevance
“…The second step focuses on implementing a fuzzy rule-based technique to identify the individual appliances at the consumer-end. In [12], Kulkarni et al collect electromagnetic field characteristics generated by various domestic devices in order to construct a distinct fingerprint for every electrical appliance. Afterward, a decision tree classifier is used to automatically manage the identification task.…”
Section: Related Workmentioning
confidence: 99%
“…The second step focuses on implementing a fuzzy rule-based technique to identify the individual appliances at the consumer-end. In [12], Kulkarni et al collect electromagnetic field characteristics generated by various domestic devices in order to construct a distinct fingerprint for every electrical appliance. Afterward, a decision tree classifier is used to automatically manage the identification task.…”
Section: Related Workmentioning
confidence: 99%
“…This method takes advantage of the fact that electrical appliances during operation generate electromagnetic fields around their enclosures. A suitable broadband antenna sensor and data acquisition system allows this disturbance to be recorded and characterized [42]. Similarly, in Reference [43], the acoustic noise produced during operation was used to identify the type of device.…”
Section: Extra-high-frequency (Ehf) Measurementsmentioning
confidence: 99%
“…Prior work in RFI can be classified into five subcategories as (1) Detection or sensing of RFI [12,13,14,15], (2) Feature extraction and characterization of RFI [11,16], (3) Modeling of RFI [11], (4) Techniques for mitigating RFI [11,17] and (5) implications of RFI in a particular field of study [9,[18][19][20][21].…”
Section: Related Workmentioning
confidence: 99%
“…Some prior work on conducted EMI has shown that these noise peaks can be used as a signature to detect appliances running on power line [23,28]. Recently [13,23] have also explored the possibility of using RFI to identify appliances operational in the vicinity. Our current work augments this existing work significantly by characterizing and modeling RFI generated from electrical and electronic appliances emitting both low-frequency and highfrequency RF emissions.…”
Section: Related Workmentioning
confidence: 99%